Pengaruh Saat Pemberian dan Konsentrasi Giberelin pada Hasil Tanaman Stroberi (Fragraria ananassa) - Iftitah, Siti Nurul; Susilowati, Yulia Eko; Zulfani, Meylana Urlia (Universitas Sebelas Maret, 2025)
Research on how gibberellin concentration and application time affect strawberry plant (Fragraria ananassa) yield. The study was conducted in Kenalan Village, Pakis District, Magelang Regency, between September 5, 2023, and December 18, 2023. The study site is 1,502 meters above sea level. A factorial experiment (3 x 4) with three replications and a completely randomized block design was employed in the study. The observation data was analyzed using variance. Further testing uses the orthogonal polynomial. The first factor is the time of application gibberellin 20, 30 and 40 dap. The second factor is gibberellin concentration 5, 10, 15 and 20 ppm. The research results showed that when administered, the response was the same for flowering age, number of flowers, fruiting age, number of fruit per plant, weight per fruit, fruit weight per plant, fruit volume, vitamin C levels, acidity levels and sugar levels. Gibberellin concentration gave the same response to all parameters. When given at 20 days after planting and a gibberellin concentration of 5 ppm, it produces the fastest flowering age, when giving it at 20 days after and a gibberellin concentration of 20 ppm produces the highest number of flowers and produces the fastest fruiting time.